The corporation as family : the gendering of corporate welfare, 1890-1930 - Mandell, Nikki (Luther Hartwell Hodges series on business, society, and the state., 2002)
Nikki Mandell explores the growth of corporate welfare programmes around the turn of the 20th century. She argues that businessmen hoped such programmes would transform conflict-ridden relations between management and labour into a harmonious partnership modelled after the Victorian family.